2020
DOI: 10.3390/math8091490
|View full text |Cite
|
Sign up to set email alerts
|

Do Science, Technology, Engineering and Mathematics (STEM) Experimentation Outreach Programs Affect Attitudes towards Mathematics and Science? A Quasi-Experiment in Primary Education

Abstract: Science, technology, engineering and mathematics (STEM) outreach programs have been widely studied in recent years considering their possible influence on future STEM career election aiming to counteract the observed decline in enrollment at university. Nonetheless, the presumed effect is not clear due to a lack of comparison with control groups. In order to fill this gap, a quasi-experimental design was adopted to analyze the effect of a STEM experimentation outreach program on 5th and 6th graders. The sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…The sample comprised 352 pupils of schools who applied for participation in the STEM experimentation outreach program "To know the science of today opens the doors of tomorrow" in the 2017-2018 academic year. The outreach programme consisted of a short intervention using scientific experiments and was described in Fernández-Cézar et al [54]. Seven schools from Castilla La Mancha, Spain, participated.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample comprised 352 pupils of schools who applied for participation in the STEM experimentation outreach program "To know the science of today opens the doors of tomorrow" in the 2017-2018 academic year. The outreach programme consisted of a short intervention using scientific experiments and was described in Fernández-Cézar et al [54]. Seven schools from Castilla La Mancha, Spain, participated.…”
Section: Participantsmentioning
confidence: 99%
“…In this study, the instruments that were part of the questionnaire were chosen according to the following criteria: originally written in Spanish to avoid translation and not lengthy to avoid possible fatigue among young students. Thus, authors have measured the attitude towards mathematics with the Auzmendi scale of attitude towards mathematics modified, ASMAm [54]. The items were evaluated on a five-point Likert scale, where 1 means totally disagree and 5 means totally agree.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we chose the survey instrument using the following criteria: Originally written in Spanish (to avoid translation and cultural mismatch) and not lengthy (to avoid the possible saturation of the young students) [39]. The form was composed of 21 items (see Table 1) extracted and modified from the Questionnaire of Opinions on Science, Technology, and Society [40].…”
Section: Instrumentmentioning
confidence: 99%
“…Some studies [34,35] found a positive correlation between self-efficacy and academic success, such that a strong sense of self-efficacy predicts increased performance and success, which then become grounds for greater self-efficacy. In particular, Kazempour [36], in a study of future teachers, points out that understanding the negative experiences and difficulties with science for pre-service teachers (PSTs)allows one to better understand their low self-efficacy and negative attitude towards science teaching, as well as the interrelation between beliefs, self-efficacy and attitude towards science if lasting changes that lead to an improvement in their teaching practices are wanted [36][37][38]. In addition, PSTs' attitudes are important, influencing students' motivation to choose STEM careers and influencing cognitive-affective variables such as self-efficacy, attitudes, motivation and beliefs [37,38].…”
Section: Introductionmentioning
confidence: 99%